Arrowheads & Stone Artifacts A practical guide for the surface collector & the amateur archaeologist - Yeager, C. G. (Pruett Publishing Company Boulder, CO, 1986)
Amateur, or avocational, archaeologists have made extraordinarily important contributions to our knowledge of prehistory. In order for them to do so, it is essential that they be able to identify the artifacts their discoveries and that, when they find sites that warrant intensive investigation, they report them to those who maintain state records and who can refer them to well-qualified professionals. This book should be very helpful for amateurs who truly care about archaeology and who wish to increase their knowledge and to contribute to the preservation and interpretation of remains of prehistoric cultures
Includes Bibliography and Index
Keywords: Archaeology -- Field works; Arrowheads -- collectors and collecting; Stone Implements -- collectors and collecting